2019
DOI: 10.1002/zaac.201800455
|View full text |Cite
|
Sign up to set email alerts
|

Two Bulky Conjugated 4′‐(4‐Hydroxyphenyl)‐4,2′:6′,4′′‐terpyridine‐based Layered Complexes: Synthesis, Structure, and Photocatalytic Hydrogen Evolution Activity

Abstract: Two new layered complexes with the formulas of {[Cu(H 2 O)(HL) 2 Cl](NO 3 )} n (1) and {[Cu(H 2 O) 2 (HL) 2 ](NO 3 ) 2 } n (2) were solvothermally synthesized by the reactions of the bulky conjugated 4Ј-(4-hydroxyphenyl)-4,2Ј:6Ј,4ЈЈ-terpyridine ligand (HL) with different Cu II salts, which were further used as photocatalysts to achieve hydrogen production from water splitting. Single-crystal structural analyses reveal that both complexes feature coplanar (4 4) layers

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…[ 26 ] On the other hand, the hydrogen production of 1 is lower than the layered Cu II ‐based CPs with 4'‐(4‐hydroxyphenyl)‐4,2':6',4''‐terpyridine ligand (2.43 and 0.53 mmol · g –1 · h –1 ) probably due to the unfavorable redox potential (–0.8 V vs. –1.1 to –0.8 V) and the absence of the d–d transition. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 26 ] On the other hand, the hydrogen production of 1 is lower than the layered Cu II ‐based CPs with 4'‐(4‐hydroxyphenyl)‐4,2':6',4''‐terpyridine ligand (2.43 and 0.53 mmol · g –1 · h –1 ) probably due to the unfavorable redox potential (–0.8 V vs. –1.1 to –0.8 V) and the absence of the d–d transition. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is found that the E g of 1 is narrower than two Cu II ‐based layered complexes with 4'‐(4‐hydroxyphenyl)‐4,2':6',4''‐terpyridine ligand (2.3 and 2.4 eV), suggesting the significance of the ligand‐field effect on optical bandgap. [ 23 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Semiconductor‐based photodegradation is considered to be the most promising strategy for eliminating water pollution due to its cleanliness and sustainable use of low cost . In photolysis applications, various homogeneous and heterogeneous photocatalysts have been widely used . In contrast to other most inorganic semiconductor catalysts, metal‐organic frameworks (MOFs), also called porous coordination) have tunable porous structures, structure design and functional modification of ligand, which have been used in various fields such as magnetic materials, gas adsorption and separation, heterogeneous catalysis, etc .…”
Section: Introductionmentioning
confidence: 99%